Effect of methylene blue on hemodynamic response in the early phase of septic shock: A case series. Issue 4 (27th January 2023) - Luis-Silva, Fabio; Menegueti, Mayra Gonçalves; Sato, Lucas; Peres, Leandro Moreira; dos Reis Sepeda, Corina; Petroski-Moraes, Bruno C.; Donadel, Mariana Dermínio; Gallo, Gabriela Bortoleto; Jordani, Maria Cecília; Mestriner, Fabiola; Becari, Christiane; Basile-Filho, Anibal; et al.
Abstract : Rationale: Methylene blue (MB) has been used to increase blood pressure in septic shock, acting on the activity of guanylate cyclase and nitric oxide synthase. Patience concerns: The aim of this study is to demonstrate the benefit of MB in early phase of septic shock. Diagnoses: We report 6 cases of patients with septic shock with up to 72 hours of evolution. Interventions: We used MB after fluid replacement, use of norepinephrine and vasopressin. Patients received a loading dose of MB and maintenance for 48 hours. Outcomes: All patients presented a reduction in the dose of vasopressors and lactate levels soon after the administration of the loading dose of MB, an effect that was maintained with the maintenance dose for 48 hours. Interleukin 6 and interleukin 8 were elevated at the beginning of the septic condition, with a progressive and marked reduction after the beginning of MB infusion, demonstrating a role of MB in reducing the inflammatory activity. Lessons: This case series suggests that MB used early in the treatment of septic shock may be useful in reducing vasopressor dose and lactate levels. Further studies are still required to further validate these findings.